Новые подходы к лечению вестибуловагинитов коров - Никогосян, Эрик; Варданян, Альберт; Григорян, Лиана; Мелконян, Жанна (ՀԱԱՀ հիմնադրամ)
Մշակվել է լայն ազդեցության հակաբիոտիկների, ախտահանիչ եւ իմունախթանիչ պատրաստւկների կիրառմամբ կովերի վեստիբուլովագինիտների բուժման նոր եղանակ: Վեստիբուլովագինիտի ախտորոշման նպատակով իրականացվել են կենդանիների կլինիկական եւ հեշտոցային հետազոտություններ։ Համանմանության սկզբունքով երկու խմբերում առանձնացվել է 7-ական գլուխ կով: Ստուգիչ խմբի կենդանիներին նշանակվել են Էթակրիդին լակտատի լուծույթ եւ Սինտոմիցինի քսուք, փորձնական խմբի կենդանիներին՝ Ցիպրոմագ 500, Միրամիստին եւ Իմունոֆան պատրաստուկներ։ Մինչեւ բուժումն սկսելը եւ բուժման ընթացքում կատարվել են հիվանդ կենդանիների արյունաբանական, արյան կենսաքիմիական ցուցանիշների եւ լեյկոբանաձեւի հետազոտություններ, ինչպես նաեւ հիվանդության ընթացքի ամենօրյա դիտարկումներ: Փորձնական խմբում վերը նշված ցուցանիշները եւ կենդանիների ընդհանուր վիճակն սկսել են կարգավորվել բուժման արդեն իսկ 2-3-րդ օրը եւ լիարժեք կարգավորվել 6-րդ օրը, իսկ ստուգիչ խմբում առողջացումն ընթացել է դանդաղ:շ The objective of this study was to develop an effective treatment protocol for bovine vestibulovaginitis using a combination of broad-spectrum antibiotics, antiseptics, and immunostimulants. Clinical and vaginal examinations were performed to diagnose vestibulovaginitis in the study subjects. Based on the principle of analogues, two groups of seven cows each were formed. The control group received conventional therapy consisting of ethacridine lactate solution and syntomycin ointment. The experimental group was administered a combination of Cipromag 500 (ciprofloxacin), Miramistin, and Immunofan. Hematological and biochemical blood analyses, including leukocyte differential counts, were conducted prior to and throughout the treatment period. Additionally, the clinical progression of the disease was monitored daily. In the experimental group, normalization of hematological and biochemical blood parameters, as well as leukocyte profiles and overall clinical condition, was observed as early as days 2–3 of treatment and was fully achieved by day 6. In contrast, recovery in the control group was slower, with a delayed return to normal parameters.
Keywords: Ветеринарная медицина и животноводство